A Bifunctional Saddle‐Shaped Small Molecule as a Dopant‐Free Hole Transporting Material and Interfacial Layer for Efficient and Stable Perovskite Solar Cells (Solar RRL 5∕2019). Issue 5 (3rd May 2019) - Lai, Xue; Meng, Fei; Zhang, Qian‐Qian; Wang, Kai; Li, Gongqiang; Wen, Yaping; Ma, Haibo; Li, Wenhui; Li, Xianqiang; Kyaw, Aung Ko Ko; Wang, Kai; Sun, Xiao Wei; et al.
Abstract : In article no.1900011, Gongqiang Li, Haibo Ma, Aung Ko Ko Kyaw, and co‐workers synthesize and systemically characterize a bifunctional saddle‐shaped small molecule, α, β‐COTh‐Ph‐OMeTAD, as a dopant‐free hole transporting material and interfacial layer in perovskite solar cells.